Effect of home visits by community health workers on complementary feeding practices among caregivers of children aged 6–23 months in 10 districts of Bangladesh - Rahman, Mahfuzur; Tariqujjaman, Md.; Ahmed, Tahmeed; Sarma, Haribondhu (Frontiers in Public Health, 2023)
Background: Suboptimal complementary feeding contributes to undernutrition among children of 6-23 months in low- and middle-income countries, like Bangladesh. Multifaceted interventions have been taken to improve complementary feeding practices but the evidence is limited about the effect of home visit by community health workers (CHW) on complementary feeding practices of the caregivers of children. Methods: We collated data from baseline and the corresponding follow-up survey done as part of an evaluation of Bangladesh Maternal, Infant and Young Child Nutrition (MIYCN) programme. We collected data on complementary feeding practices, using a 24-hour recall questionnaire. Age-appropriate dietary diversity, minimum meal frequency, and minimum acceptable diet were assessed based on recommended food consumption as per the child’s age. To understand the effect of CHWs’ visits on complementary feeding practices, we performed Generalized Estimating Equation (GEE) procedure for dealing with correlated data and adjusted other covariates. Results: A total of 758 and 745 caregivers of children aged 6-23 months participated in the baseline and follow-up survey respectively. Complementary feeding practices were improved in one year of programme implementation; dietary diversity increased from 46% to 54%, minimum meal frequency from 82% to 91%, and minimum acceptable diet from 41% to 53%. Caregivers of children who received the visit of CHWs in the last12 months prior to the day of the follow-up survey were more likely (AOR 1.51; 95% CI 1.10-2.10) to maintain dietary diversity in the feeding practices for their children compared to the caregivers who were not exposed to the visit of the CHWs in the last 12 months. The likelihood of maintaining minimum acceptable diet in the feeding practices was 1.57 times higher (AOR 1.57; 95% CI 1.14-2.17) among the caregivers who were exposed to the visit of the CHWs in the last 12 months compared to the caregivers who were not exposed to the CHW’s visit in the last 12 months. Conclusion: Integration of promotional activities of complementary feeding practices with the mainstream nutrition programme can be instrumental in optimizing complementary feeding practices among the caregivers of under-five children. However, home visits by CHWs should be prioritized in such an integrated programme.